A Nanojunction Polymer Photoelectrode for Efficient Charge Transport and Separation. (12th June 2017) - Ruan, Qiushi; Luo, Wenjun; Xie, Jijia; Wang, Yiou; Liu, Xu; Bai, Zhiming; Carmalt, Claire J.; Tang, Junwang
Abstract: A metal‐free photoanode nanojunction architecture, composed of B‐doped carbon nitride nanolayer and bulk carbon nitride, was fabricated by a one‐step approach. This type of nanojunction (s‐BCN) overcomes a few intrinsic drawbacks of carbon nitride film (severe bulk charge recombination and slow charge transfer). The top layer of the nanojunction has a depth of ca. 100 nm and the bottom layer is ca. 900 nm. The nanojunction photoanode results into a 10‐fold higher photocurrent than bulk graphitic carbon nitride (G‐CN) photoanode, with a record photocurrent density of 103.2 μA cm −2 at 1.23 V vs. RHE under one sun irradiation and an extremely high incident photon‐to‐current efficiency (IPCE) of ca. 10 % at 400 nm. Electrochemical impedance spectroscopy, Mott–Schottky plots, and intensity‐modulated photocurrent spectroscopy show that such enhancement is mainly due to the mitigated deep trap states, a more than 10 times faster charge transfer rate and nearly three times higher conductivity due to the nanojunction architecture.